PENGARUH CITRA MEREK, KUALITAS PRODUK, HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (Studi Pada Lapis Kukus Pahlawan di Toko Noer Raya Gresik) - Indah Nahdiyah, Zumro; Vitriya, Rezza (Sekolah Tinggi Ilmu Ekonomi NU Trate Gresik, 2023)
This study aims to examine the influence of brand image, product quality, price and service quality on customer satisfaction. The object of this study is the customer of Lapis Kukus Pahlawan in Store Noer Raya Gresik. A total of 95 data were collected using questionnaires with non-probality sampling technique using purposive sampling. Data analysis was conducted using multiple linear regression analysis method with statistical test application version 20. T-test results showed that brand image, price, and service quality have a positive and significant effect on customer satisfaction of Lapis Kukus Pahlawan, while product quality does not have a significant effect on customer satisfaction of Lapis Kukus Pahlawan. The result of f Test shows that brand image, product quality, price, and service quality have a positive and significant effect on customer satisfaction of Lapis Kukus Pahlawan.